In Silico PASS Predictions and Exploration of Antioxidant and Anti-inflammatory Activity of Citrus Karna Raf. Fruit - Prasad JAMKHANDE; Mahavir GHANTE; Rajeshwar KSHIRSAGA (Medeniyet Medical Journal)
Objective: Inflammation and oxidative stress are major factors in the development of many disorders. Natural antioxidants present in plants can interrupt, decrease, or reduce the oxidation of components sensitive to oxidative processes by scavenging free radicals and lowering oxidative stress. Most anti-inflammatory agents used in the management of inflammatory disorders diminish oxidative damage. The biological potential of Citrus karna Raf. remains undisclosed, despite its richness in several bioactive compounds. Methods: The methanolic extract was evaluated for quantitative phytochemical analysis and antioxidative efficacy using 1,1-diphenyl-2-picrylhydrazyl radical and hydrogen peroxide scavenging activity. A carrageenan-induced paw edema model was employed to evaluate the anti-inflammatory potential as antioxidants exert anti-inflammatory effects. In silico prediction of activity spectra for substance predictions were performed to understand the possible mechanism of action of phytochemicals. Results: Citrus karna methanolic extract (CKME) showed dose-dependent radical scavenging effects. The powerful scavenging activity of CKME could be due to the diverse polyphenolic compounds such as ascorbic acid, beta-carotene, and naringin. In addition, the percentage inhibition of paw edema and swelling was observed in CKME-treated rats and mice, which is the same as that of standard drug-treated groups. The Pa value of ascorbic acid, beta-bisabolene, linalool, and naringin is more than 0.7 which shows that these phytoconstituents might contribute to the anti-inflammatory action of extract samples such as CKME. Conclusions: Our findings shows that CKME possess strong antioxidant and anti-inflammatory effects. The richness of plants in polyphenolics such as flavonoids might be a contributing factor for these potential effects.